2023
DOI: 10.2174/2405461507666220516092814
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Copper Nanoparticles by Using Plant Extracts and their Biomedical Applications – An Extensive Review

Abstract: In recent years, the green synthesis of different metal nanoparticles has become a substantial technique for the synthesis of different essential nanoparticles and their potential applications in technological, industrial along with biomedical fields. Among the several essential nanoparticles, copper nanoparticles (CuNPs) have been attracted enormous attention for their wide range of applications like production of gas sensors, solar cells, high temperature superconductors as well as drug delivery materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
2
2
0
Order By: Relevance
“…In contrast, several functional groups present in the P. guajava extract, as depicted in Figure 4a, are absent in P.g-CuNPs. The missing functional groups, along with those exhibiting decreased and increased wavenumbers, likely play roles in the reduction, capping, and stabilization of the synthesized copper nanoparticles, aligning with Javed et al [4] and Rakshit et al [40] . The latter authors reported that plant extracts, containing phytometabolites like phenols and flavonoids, act as stabilizing or reducing agents in the copper salt reduction process [41,40] .…”
Section: Atr-ftir Spectroscopy Of P Guajava Extract and Synthesized P...supporting
confidence: 76%
See 2 more Smart Citations
“…In contrast, several functional groups present in the P. guajava extract, as depicted in Figure 4a, are absent in P.g-CuNPs. The missing functional groups, along with those exhibiting decreased and increased wavenumbers, likely play roles in the reduction, capping, and stabilization of the synthesized copper nanoparticles, aligning with Javed et al [4] and Rakshit et al [40] . The latter authors reported that plant extracts, containing phytometabolites like phenols and flavonoids, act as stabilizing or reducing agents in the copper salt reduction process [41,40] .…”
Section: Atr-ftir Spectroscopy Of P Guajava Extract and Synthesized P...supporting
confidence: 76%
“…The missing functional groups, along with those exhibiting decreased and increased wavenumbers, likely play roles in the reduction, capping, and stabilization of the synthesized copper nanoparticles, aligning with Javed et al [4] and Rakshit et al [40] . The latter authors reported that plant extracts, containing phytometabolites like phenols and flavonoids, act as stabilizing or reducing agents in the copper salt reduction process [41,40] . and biomolecules in P.guajava leaf extracts, as well as the presence of secondary metabolites in leaves and fruit extracts.…”
Section: Atr-ftir Spectroscopy Of P Guajava Extract and Synthesized P...supporting
confidence: 76%
See 1 more Smart Citation
“…Nanoparticles have innate cytotoxic properties, which contribute to their anticancer and antibacterial efficacy against cancer cells and other microbes, including bacteria and fungi [ 13 ]. Moreover, CaONPs have already been biosynthesized from extracts from various plants, they can be used as capping and reducing agents, and their antimicrobial potential has been recognized for decades in the medical field, from both traditional and scientific perspectives [ 6 ].…”
Section: Introductionmentioning
confidence: 99%